1995
DOI: 10.3354/meps129141
|View full text |Cite
|
Sign up to set email alerts
|

The impact of habitat disturbance by scallop dredging on marine benthic communities:what can be predicted from the results of experiments?

Abstract: Field experiments were conducted on 2 subtidal sandflats to identify the short-term impacts of commercial scallop dredging on macrobenthic communities. The 2 sites (1400 m2) were situated 14 km apart, both at about 24 m depth, with similar exposure aspects and were characterised by infaunal communities dominated by small and short-lived species. Prior to dredging, preliminary sampling failed to reveal significant differences in the density of common macrofauna within each site, although community composition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(99 citation statements)
references
References 31 publications
2
96
0
Order By: Relevance
“…Before proceeding, we should make it clear that we share the opinions o~ ~ Dayton et al (1995), Jackson et al (9001), and Steneck and Sala (2005) who have argued that virtually all of the published predation studies have been carried out under conditions that are fundamentally difterent tkom those that existed when most predator-prey relationships evolved. This is because humans have removed extraordinary quantities of large consumers from the world's coastal oceans, so that many are ecologically extinct, and some have been so tor as long as several hundred years (see examples in Dayton et al 1995Dayton et al , 1998Jackson et al 2001;Myers and Worm 2003;Steneck and Sala 2005).…”
Section: Data Sources and A Caveatmentioning
confidence: 99%
See 2 more Smart Citations
“…Before proceeding, we should make it clear that we share the opinions o~ ~ Dayton et al (1995), Jackson et al (9001), and Steneck and Sala (2005) who have argued that virtually all of the published predation studies have been carried out under conditions that are fundamentally difterent tkom those that existed when most predator-prey relationships evolved. This is because humans have removed extraordinary quantities of large consumers from the world's coastal oceans, so that many are ecologically extinct, and some have been so tor as long as several hundred years (see examples in Dayton et al 1995Dayton et al , 1998Jackson et al 2001;Myers and Worm 2003;Steneck and Sala 2005).…”
Section: Data Sources and A Caveatmentioning
confidence: 99%
“…This is because humans have removed extraordinary quantities of large consumers from the world's coastal oceans, so that many are ecologically extinct, and some have been so tor as long as several hundred years (see examples in Dayton et al 1995Dayton et al , 1998Jackson et al 2001;Myers and Worm 2003;Steneck and Sala 2005). Because we believe that most coastal ecosystems are now devoid, or nearly devoid, of apex predators, as well as many mid and lower order consumers (Panly et al 1998), it is unlikely that any of the published studies were conducted in ecosystems whose species composition was simile" to that prior to human intervention.…”
Section: Data Sources and A Caveatmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Pranovi et al (2004) in a multidisciplinary study of the immediate effects of mechanical clam harvesting in the Venice lagoon detected a significant decrease in the total number of individuals after the haul. Thrush et al (1995) observed a decrease in macrofaunal taxa due to scallop dredging and Kaiser and Spencer (1996) reported a general decrease in biodiversity after beam trawling.…”
Section: Biological Impactsmentioning
confidence: 99%
“…Biodiversity loss may persist over long periods of time, namely due to the reduction of habitat complexity, resulting from the removal of tubicolous organisms and epibenthic species (Dayton et al, 1995;Kaiser et al, 2000). These organisms are particularly important as they provide protection for commercial species, and their removal will potentially affect fisheries .…”
Section: Biological Impactsmentioning
confidence: 99%